#TITLE_ALTERNATIVE# - SULISTYO PUTRO (NIM 20504028), HERDAYANTO
Waste dumping has always been a major problem in any development countries, especially Indonesia. Waste composition in every city showed that about 70% of total municipal waste is organic waste and 60% of them are made from residential waste bin. Organic waste treatment has become notable because it might reduced amount of waste stack and solved municipal waste problem extensively. The most economic and environmental friendly of organic waste treatment is composting process. Composting turns easily degradable organic matter into stable matter containing a humic-like substance by passing through a thermophilic stage. Previous research shown that there was changing on microbial communities during composting process. While Initiation phase were dominated by mesophilic microbes and then changed to thermophilic microbes at the main phase. Afterwards, new mesophilic microbes were presence during cooling and maturing phase. This pattern was exposed by significant temperature changes during each step of composting phases. Many methods have been developed to regain the diverse species of microbes during composting process. In this research, physicochemistry properties were observed during composting process and showed that there were changing during the composting process. The crucial physicochemistry properties are temperature and pH for determining composting phases and also provided fast, easy and simple data. The aim of this research was to study physicochemistry properties during composting process and deducts the dynamic pattern of the microbial communities of habitating during the process. First step of the research was to design medium scaled composting reactor. The reactor was used for composting process from traditional market waste. Temperature observation during the process showed that the highest temperature was gained at 43,3 oC and maturing process took 3-4 months. The low temperature reached at composting process might due to the small capacity of reactor and the failure to maintain aerobic system which inhibits thermophilic state. Since the maximum temperature was unable to reach thermophilic state, the compost sample in reactor are not used in further observation. Another compost was collected to determine the sample points for the research. The compost samples were determined by the observation of temperature and pH changes for a whole month. Each of sample steps were represented the composting phase. The samples were taken from TPS Cibangkong that showed maximum composting temperature at 70 oC. The changes of pH were also monitored as from pH 6 to pH 10 then slightly went down to pH 8. Samples were taken on day 3, day 14, and day 28 which had average temperature at 44oC, 69,5oC, 37,5oC. Based on the temperature changes, mesophilic bacteria might exist at initiation phase, afterward the thermophilic bacteria replacing on the sample at main phase was reached, followed by cooling and maturing phase with probably the new mesophilic bacteria was replacing the thermophiles. According on pH change, probably due to the mesophilic bacteria in initiation state were used easily degradable substrates and proliferate, also in results of a decrease in TDOC (total dissolve organic carbon). Subsequently in main phase, proteolysis bacteria degarded protein and produced NH3 gas. After that, new mesophilic bacteria were degraded the remaining complex compounds since easily degradable compounds inducing temperature increase were lost.